Aplicación de rizobacterias en el desarrollo vegetativo del cultivo de tomate de riñón (Solanum lycopersicum L.) y sobre las propiedades físicas, químicas y biológicas del suelo bajo condiciones de invernadero en la Quinta experimental La Argelia - Ramón Pineda, Sayro Geovanny (2024)
In the present research, the vegetative development of the kidney tomato crop was evaluated in response to the application of rhizobacteria and the physical, chemical and microbiological properties of the soil were determined before and after their application, under greenhouse conditions at La Argelia Experimental Farm of the National University of Loja. The trial was developed under a Completely Randomized Design (CRD) with five treatments and four replications. The agronomic variables evaluated were plant height, stem diameter, root length, days to flowering, dry biomass and soil physical, chemical and microbiological properties. The effect of the treatments on the dependent variables was evaluated by means of an Analysis of Variance (ANOVA) complemented with Multiple Comparison Tests (Tukey at 0.05 %). The results obtained through the inoculation of plant growth promoting rhizobacteria (PGPR) showed positive effects on the kidney tomato crop, where all the parameters measured on vegetative development were significantly increased, such as: plant height by 29.26 cm, diameter by 1.41 mm, root length by 7 cm and dry biomass by 18.05 g compared to the absolute control, while days to flowering were reduced by 3.75 compared to the absolute control under controlled conditions. Regarding the inoculation of rhizobacteria on soil properties, it was determined that the chemical properties were increased in the levels of macro and micronutrients (N by 9.94%, P by 30.33%, K by 0.03%, B by 0.46%, Fe by 8.4% and Mg by 0.65%, as well as improving the soil pH by 0.08%, M. O by 0.29 % and CEC by 3.7 meq/100g), as well as the microbiological properties (bacteria) increased by 173 CFU/ml and the physical properties decreased the bulk density values by 0.27 g/cm3 and the percentage of porosity increased by 10 % with respect to the initial situation of the experiment.